Enhanced ionization of embedded clusters by electron-transfer-mediated decay in helium nanodroplets - LaForge, Aaron; Stumpf, Vasili; Gokhberg, Kirill; von Vangerow, J.; Stienkemeier, F.; Kryzhevoi, Nikolai V.; O’Keeffe, P.; Ciavardini, A.; Krishnan, S. R.; Coreno, M.; Prince, K. C.; Richter, R.; et al. (Physical review letters, 2016)
We report the observation of electron-transfer-mediated decay (ETMD) involving magnesium (Mg) clusters embedded in helium (He) nanodroplets. ETMD is initiated by the ionization of He followed by removal of two electrons from the Mg clusters of which one is transferred to the He ion while the other electron is emitted into the continuum. The process is shown to be the dominant ionization mechanism for embedded clusters for photon energies above the ionization potential of He. For Mg clusters larger than five atoms we observe stable doubly ionized clusters. Thus, ETMD provides an efficient pathway to the formation of doubly ionized cold species in doped nanodroplets.